Acaricidal action of β-caryophyllene via COX-2/PGE2 suppression and octopaminergic receptor upregulation in the ovary of Rhipicephalus annulatus - Srikanth Immadi; Subramaniam Kathiravan; Panicker Devayani Ramachandran; Karapparambu Gopalan Ajith Kumar; Anju Varghese; Chundayil Kalarikkal Deepa; D Ranjith; Srikant Ghosh; Sanis Juliet; Reghu Ravindran (Next Research, 2026)

Correction: Nanotechnology-enhanced Natural Products for Cancer Chemoprevention: Molecular Mechanisms and Clinical Translation - Rajat Nath; Sibashish Kityania; Deepa Nath; Jayanta Kumar Patra; Emran Habibi; Satyajit D. Sarker; Anupam Das Talukdar; Lutfun Nahar (The AAPS Journal, 2026)

Enhancing Oryza sativa Growth with a Genome-Characterized Bacillus velezensis SNR14-4, a Marine Strain Isolated from Fish Gills - Nambillipadath R. Rashid Muhammed; Sethu Madhavan; Niveditha D. Neroth; Deepa John; Sini Hariharan; Kottayath G. Nevin (Agricultural Research, 2026)

Nanotechnology-enhanced Natural Products for Cancer Chemoprevention: Molecular Mechanisms and Clinical Translation - Rajat Nath; Sibashish Kityania; Deepa Nath; Jayanta Kumar Patra; Emran Habibi; Satyajit D. Sarker; Anupam Das Talukdar; Lutfun Nahar (The AAPS Journal, 2026)

Bringing the Teaching Close to Home: Implementation of a Near-Peer Model for Introductory Hematology-Oncology Fellowship Lecture Series - Jonathan L. Berry; Lauren O’Loughlin; Anthony Iacoviello; Kevin Barnum; Barbara D. Lam; Matthew Chase; Reed E. Drews; Jason A. Freed; Rushad Patell; Deepa Rangachari (Journal of Cancer Education, 2026)

Development of an in-situ forming implant system for levodopa and carbidopa for the treatment of parkinson’s disease - Deepa D. Nakmode; Sadikalmahdi Abdella; Yunmei Song; Sanjay Garg (Drug Delivery and Translational Research, 2025)
Long-acting injectables have gained attraction as a system for treating chronic conditions due to their increased efficacy, safety, and patient compliance. Currently, patients with Parkinsons need to administer oral medications multiple times a day which imposes the significant risk of non-compliance. This study aimed to design an in-situ implant-forming system for controlled delivery of levodopa and carbidopa for up to 1 week which will reduce the need for multiple dosing. The combination of poly-lactic-co-glycolic acid (PLGA 50:50 ) and Eudragit L-100 was used to prepare the implants and the formulation was optimized to achieve a controlled release over 7 days. The optimized formulation containing 26% PLGA and 6% Eudragit L 100 displayed a favorable release profile and injectability with low viscosity. The optimized formulation in vitro release study revealed an initial burst of 34.17% and 37.16% for levodopa and carbidopa in the first 24 h and about 92% and 81% release within 7 days. A good correlation was observed between the in-vitro drug release data and ex-vivo drug release with a correlation coefficient of 0.91 for levodopa and 0.90 for carbidopa. Viscosity analysis showed the Newtonian behavior of the formulation. Syringeability analysis of the formulation showed that the maximum force required for expelling the formulation was 32.98 ± 0.72 N using a 22 G needle. The in-vitro degradation studies revealed 81.89% weight loss of implant in 7 days. The prepared formulation was assessed for in-vivo performance using a convolution modeling technique using a convolve function in R software. The predicted AUC 0-∞ h for the in-situ forming implant was 26505.5 ng/ml with Cmax, 399.3 ng/ml, and Tmax 24 h assuming 100% bioavailability. The results justify that the prepared in-situ implant forming system can be a promising system for the delivery of levodopa and carbidopa for Parkinson’s patients.

Reconstitution of natural products biosynthetic pathways using cell- free synthetic biology - Deepa D Acharya; Krishna Madduri; Jeremy McFadden; Jade Bing; Paul Ketterer; Babu Raman (Phytochemistry Letters, 2025)

Tailored NiSx/BaNiO3 bilayer for enhanced oxygen evolution reaction in alkaline seawater - J. Junita; D. Jayalakshmi; S. Deepa Priya; Byung Chul Kim; John D. Rodney (Chemical Engineering Journal, 2025)

Exploring climate-driven phenological mismatches in pears, pests and natural enemies: a multi-model approach - Laura A. Reeves; Tim Belien; Deepa Senapathi; Michael P. D. Garratt; Michelle T. Fountain (Journal of Pest Science, 2025)
Pear psyllid ( Cacopsylla pyri ) is the dominant pest of UK pear orchards, with an estimated cost of £5 million per annum. Insecticide withdrawal and increased pesticide resistance of C. pyri have led many growers to depend more on natural enemies for pest management, including earwigs. However, there is concern how phenological events may shift with future climate change, which may result in phenological mismatches. This study aimed to determine shifts in timing of phenological events within an agroecosystem and predict phenological mismatches or synchronies between trophic levels. We evaluated three models: the C. pyri phenology model, the earwig degree day model and the PhenoFlex model (flowering time). Phenological events predicted by models included: first, full and last flowering time for Pyrus communis ; peak psyllid abundance date for first-generation (G1) C. pyri nymphs and second-generation (G2) eggs, nymphs and adults; and peak abundance date for stage 4 Forficula auricularia and adults. Findings indicated that the timing of phenological events was advancing for all trophic levels, becoming significantly earlier under the current time period. Furthermore, predictions indicated that timing events would continue to advance under the RCP8.5 scenario. However, not all phenological events advanced at the same rate; the date of peak C. pyri G1 nymph abundance advanced at a higher rate than full flowering time, which could result in a phenological mismatch by 2071. Conversely, C. pyri and F. auricularia showed phenological synchrony, with peak abundance dates advancing at a similar rate, which could be beneficial for future biological control.

Correction: Long-acting parenteral formulations of hydrophilic drugs, proteins, and peptide therapeutics: mechanisms, challenges, and therapeutic benefits with a focus on technologies - Deepa D. Nakmode; Baljinder Singh; Sadikalmahdi Abdella; Yunmei Song; Sanjay Garg (Drug Delivery and Translational Research, 2025)

Long-acting parenteral formulations of hydrophilic drugs, proteins, and peptide therapeutics: mechanisms, challenges, and therapeutic benefits with a focus on technologies - Deepa D. Nakmode; Baljinder Singh; Sadikalmahdi Abdella; Yunmei Song; Sanjay Garg (Drug Delivery and Translational Research, 2025)
Despite being the most widely prescribed formulation, oral formulations possess several limitations such as low adherence, low bioavailability, high toxicity (in the case of anticancer drugs), and multiple-time administration requirements. All these limitations can be overcome by long-acting injectables. Improved adherence, patient compliance, and reduced relapse have been observed with long-acting formulation which has increased the demand for long-acting injectables. Drugs or peptide molecules with oral bioavailability issues can be easily delivered by long-acting systems. This review comprehensively addresses the various technologies used to develop long-acting injections with a particular focus on hydrophilic drugs and large molecules as well as the factors affecting the choice of formulation strategy. This is the first review that discusses the possible technologies that can be used for developing long-acting formulations for hydrophilic molecules along with factors which will affect the choice of the technology. Furthermore, the mechanism of drug release as well as summaries of marketed formulations will be presented. This review also discusses the challenges associated with the manufacturing and scale-up of the long-acting injectables. Graphical abstract

Genetic diversity and population structure analysis in tamarind (Tamarindus indica L.) using SCoT and SRAP markers - C. Kanupriya; G. Karunakaran; Pritee Singh; R. Venugopalan; Deepa Samant; D. C. Lakshmana Reddy; K. Prakash (Genetic Resources and Crop Evolution, 2025)

Intraguild Predation or Spatial Separation? The efficacy and Interactions of Two Natural Enemy Species for the Biological Control of Pear Psyllid (Cacopsylla pyri) - Laura A. Reeves; Michelle T. Fountain; Michael P. D. Garratt; Deepa Senapathi (Journal of Insect Behavior, 2024)
Pear psyllid ( Cacopsylla pyri ) is a persistent pest to the pear industry; with an estimated cost of £5 million per annum in the UK alone. This phloem feeding insect is resistant to a large proportion of approved pesticides, necessitating the use of alternative control strategies. Many pear growers practice integrated pest management (IPM) of pear psyllid, focusing on maximizing natural enemy populations, whilst minimizing the use of agrochemical sprays. The anthocorid Anthocoris nemoralis and the European earwig Forficula auricularia are particularly effective at controlling pear psyllid populations during the summer months. Despite the effectiveness of both natural enemies, there is a lack of understanding on whether both species should be promoted together or separately, due to the risk of intraguild predation (IGP) or interference competition. Furthermore, abiotic factors including temperature may influence both behaviors, altering activity level and niche overlap. Although IGP and interference competition have been documented between multiple species of natural enemies neither have been studied between these two specific predators. Using microcosm experiments, olfactometer assays and survival analyses this study demonstrated whether A. nemoralis and F. auricularia can be used in synchrony to control pear psyllid. Results indicated that IGP is present; F. auricularia will consume A. nemoralis when predators are not spatially separate and in absence of psyllid prey. There was no evidence for interference competition, although both predators consumed more prey at higher temperatures. This confirms that pear growers can encourage both predators for the control of pear psyllid without losing predation efficacy.

Steroids and Epicoccarines from Penicillium aurantiancobrunneum - Charmaine A. Lindsay; Choon Y. Tan; Deepa Krishnan; Dmitriy Uchenik; Gerardo D. Anaya Eugenio; Eric D. Salinas; Esperanza J. Carcache de Blanco; A. Douglas Kinghorn; Harinantenaina L. Rakotondraibe (Phytochemistry Letters, 2024)

Extraction of Natural Pigment Curcumin from Curcuma Longa: Spectral, DFT, Third-order Nonlinear Optical and Optical Limiting Study - S. Deepa; S. Madhu; S. Devasenan; G. Murali; Pattath D. Pancharatna; M. Maaza; K. Kaviyarasu; S. Jeyaram (Journal of Fluorescence, 2024)

A whole ecosystem approach to pear psyllid (Cacopsylla pyri) management in a changing climate - Laura A. Reeves; Michael P. D. Garratt; Michelle T. Fountain; Deepa Senapathi (Journal of Pest Science, 2024)
Whole ecosystem-based approaches are becoming increasingly common in pest management within agricultural systems. These strategies consider all trophic levels and abiotic processes within an ecosystem, including interactions between different factors. This review outlines a whole ecosystem approach to the integrated pest management of pear psyllid ( Cacopsylla pyri Linnaeus) within pear ( Pyrus communis L.) orchards, focusing on potential disruptions as a result of climate change. Pear psyllid is estimated to cost the UK pear industry £5 million per annum and has a significant economic impact on pear production globally. Pesticide resistance is well documented in psyllids, leading to many growers to rely on biological control using natural enemies during the summer months. In addition, multiple insecticides commonly used in pear psyllid control have been withdrawn from the UK and Europe, emphasising the need for alternative control methods. There is growing concern that climate change could alter trophic interactions and phenological events within agroecosystems. For example, warmer temperatures could lead to earlier pear flowering and pest emergence, as well as faster insect development rates and altered activity levels. If climate change impacts pear psyllid differently to natural enemies, then trophic mismatches could occur, impacting pest populations. This review aims to evaluate current strategies used in C. pyri management, discuss trophic interactions within this agroecosystem and highlight potential changes in the top-down and bottom-up control of C. pyri as a result of climate change. This review provides a recommended approach to pear psyllid management, identifies evidence gaps and outlines areas of future research.

Integrating Multiscale Geospatial Analysis for Monitoring Crop Growth, Nutrient Distribution, and Hydrological Dynamics in Large-Scale Agricultural Systems - Olatunde D. Akanbi; Deepa C. Bhuvanagiri; Erika I. Barcelos; Arafath Nihar; Brian Gonzalez Hernandez; Jeffrey M. Yarus; Roger H. French (Journal of Geovisualization and Spatial Analysis, 2024)
Monitoring crop growth, soil conditions, and hydrological dynamics are imperative for sustainable agriculture and reduced environmental impacts. This interdisciplinary study integrates remote sensing, digital soil mapping, and hydrological data to elucidate intricate connections between these factors in the state of Ohio, USA. Advanced spatiotemporal analysis techniques were applied to key datasets, including the MODIS sensor satellite imagery, USDA crop data, soil datasets, Aster GDEM, and USGS stream gauge measurements. Vegetation indices derived from MODIS characterized crop-specific phenology and productivity patterns. Exploratory spatial data analysis show relationships of vegetation dynamics and soil properties, uncovering links between plant vigor, edaphic fertility, and nutrient distributions. Correlation analysis quantified these relationships and their seasonal evolution. Examination of stream gauge data revealed insights into spatiotemporal relationships of nutrient pollution and stream discharge. By synthesizing diverse geospatial data through cutting-edge data analytics, this work illuminated complex interactions between crop health, soil nutrients, and water quality in Ohio. The methodology and findings provide actionable perspectives to inform sustainable agricultural management and environmental policy. This study demonstrates the significant potential of open geospatial resources when integrated using a robust spatiotemporal framework. Integrating additional measurements and high-resolution data sources through advanced analytics and interactive visualizations could strengthen these insights.

Intracellular iron accumulation facilitates mycobacterial infection in old mouse macrophages - Stephen K. Kotey; Xuejuan Tan; Owen Fleming; Ramakrishnama Raju Kasiraju; Audrey L. Dagnell; Kyle N. Van Pelt; Janet Rogers; Steven D. Hartson; Nidheesh Thadathil; Ramasamy Selvarani; Rojina Ranjit; Sreemathi Logan; et al. (GeroScience, 2023)
Aging has a significant impact on the immune system, leading to a gradual decline in immune function and changes in the body’s ability to respond to bacterial infections. Non-tuberculous mycobacteria (NTM), also known as atypical mycobacteria or environmental mycobacteria, are commonly found in soil, water, and various environmental sources. While many NTM species are considered opportunistic pathogens, some can cause significant infections, particularly in individuals with compromised immune systems, such as older individuals. When mycobacteria enter the body, macrophages are among the first immune cells to encounter them and attempt to engulf mycobacteria through a process called phagocytosis. Some NTM species, including Mycobacterium avium ( M. avium ) can survive and replicate within macrophages. However, little is known about the interaction between NTM and macrophages in older individuals. In this study, we investigated the response of bone marrow–derived macrophage (BMMs) isolated from young (5 months) and old (25 months) mice to M. avium serotype 4, one of the main NTM species in patients with pulmonary NTM diseases. Our results demonstrated that BMMs from old mice have an increased level of intracellular iron and are more susceptible to M. avium serotype 4 infection compared to BMMs from young mice. The whole-cell proteomic analysis indicated a dysregulated expression of iron homeostasis–associated proteins in old BMMs regardless of mycobacterial infection. Deferoxamine, an iron chelator, significantly rescued mycobacterial killing and phagolysosome maturation in BMMs from old mice. Therefore, our data for the first time indicate that an intracellular iron accumulation improves NTM survival within macrophages from old mice and suggest a potential application of iron-chelating drugs as a host-directed therapy for pulmonary NTM infection in older individuals.

Characterization of novel mouse models to study the role of necroptosis in aging and age-related diseases - Ramasamy Selvarani; Hoang Van Michelle Nguyen; Nidheesh Thadathil; Roman F. Wolf; Willard M. Freeman; Christopher D. Wiley; Sathyaseelan S. Deepa; Arlan Richardson (GeroScience, 2023)
To study the impact of necroptosis-induced chronic inflammation on age-related diseases and aging, two knockin mouse models ( Ripk3 -KI and Mlkl -KI) were generated that overexpress two genes involved in necroptosis ( Ripk3 or Mlkl ) when crossed to Cre transgenic mice. Crossing Ripk3 -KI or Mlkl -KI mice to albumin-Cre transgenic mice produced hepatocyte specific hRipk3 -KI or hMlkl -KI mice, which express the two transgenes only in the liver. Ripk3 and Mlkl proteins were overexpressed 10- and fourfold, respectively, in the livers of the hRipk3 -KI or hMlkl -KI mice. Treating young (2-month) hRipk3 -KI or hMlkl -KI mice with carbon tetrachloride (CCl 4 ), a chemical inducer of oxidative stress, resulted in increased necroptosis (Mlkl-oligomers) and inflammation in the liver compared to control mice receiving CCl 4 . Mlkl-oligomerization also was significantly increased in old (18-month) hRipk3 -KI and hMlkl -KI mice compared to old control (Cre negative, Ripk3 -KI and Mlkl -KI) mice. The increase in necroptosis was associated with an increase in inflammation, e.g., inflammatory cytokines (TNFα, IL-6) and macrophage markers (F4/80, CD68). Importantly, steatosis (triglycerides) and fibrosis (e.g., picrosirius red staining, hydroxyproline levels, and transcripts for TGFβ, Col1α1, and Col3α1) that increase with age were significantly higher in the livers of the old hRipk3 -KI or hMlkl -KI mice compared to old control mice. In addition, markers of cellular senescence were significantly increased in the livers of the old hRipk3 -KI and hMlkl -KI mice. Thus, the first mouse models have been developed that allow researchers to study the impact of inducing necroptosis in specific cells/tissues on chronic inflammation in aging and age-related diseases.

Functional and Behavioral Responses of the Natural Enemy Anthocoris nemoralis to Cacopsylla pyri, at Different Temperatures - Laura A. Reeves; Michael P. D. Garratt; Michelle T. Fountain; Deepa Senapathi (Journal of Insect Behavior, 2023)
Anthocoris nemoralis is the dominant predator of pear sucker ( Cacopsylla pyri ) in the UK. Anthocoris nemoralis migrates into orchards in spring or is introduced as a biocontrol agent, reaching peak population levels in July-August, contributing to effective control of summer pear sucker populations. However, due to temperature dependent development and metabolism there are concerns that C. pyri populations or feeding rates may increase due to changing climatic conditions. Thus, how A. nemoralis responds to temperature, impacts its ability as a biocontrol agent. Functional response assays, monitoring attack rate and handling time of A. nemoralis and behavioral assays, using Ethovision tracking software occurred, to assess the impact of temperature on predation. Experiments were conducted at current and future July-August mean temperatures, predicted using RCP4.5 and RCP8.5 (medium and high, representative concentration pathway) emissions scenarios, using 2018 UK Climate Projections (UKCP18). All treatments demonstrated a Type II functional response, with female anthocorids demonstrating shorter handling times and higher attack rates than males. Males showed longer prey handling times at 18 °C compared to 23 °C and more time was spent active at lower temperatures for both sexes. Females did not show significant differences in attack rate or handling time in response to temperature. Overall prey consumption was also not significantly affected by temperature for either sex. This study suggests that anthocorids are likely to remain effective natural enemies under future predicted temperatures, due to non-significant differences in prey consumption.

Rapid assessment of insect pollination services to inform decision‐making - Fabrizia Ratto; Tom D. Breeze; Lorna J. Cole; Michael P. D. Garratt; David Kleijn; Bill Kunin; Denis Michez; Rory O'Connor; Jeff Ollerton; Robert J. Paxton; Guy M. Poppy; Simon G. Potts; et al. (Conservation Biology, 2022)
Pollinator declines have prompted efforts to assess how land‐use change affects insect pollinators and pollination services in agricultural landscapes. Yet many tools to measure insect pollination services require substantial landscape‐scale data and technical expertise. In expert workshops, 3 straightforward methods (desk‐based method, field survey, and empirical manipulation with exclusion experiments) for rapid insect pollination assessment at site scale were developed to provide an adaptable framework that is accessible to nonspecialist with limited resources. These methods were designed for TESSA (Toolkit for Ecosystem Service Site‐Based Assessment) and allow comparative assessment of pollination services at a site of conservation interest and in its most plausible alternative state (e.g., converted to agricultural land). We applied the methods at a nature reserve in the United Kingdom to estimate the value of insect pollination services provided by the reserve. The economic value of pollination services provided by the reserve ranged from US$6163 to US$11,546/year. The conversion of the reserve to arable land would provide no insect pollination services and a net annual benefit from insect‐pollinated crop production of approximately $1542/year (US$24∙ha –1 ∙year –1 ). The methods had wide applicability and were readily adapted to different insect‐pollinated crops: rape ( Brassica napus ) and beans ( Vicia faba ) crops. All methods were rapidly employed under a low budget. The relatively less robust methods that required fewer resources yielded higher estimates of annual insect pollination benefit.

Sequential Profiling of Anti-SARS CoV-2 IgG Antibody in Post COVID-19 Patients - Ajaikumar Sukumaran; Rhema Elizabeth Thomas; R. Arun Krishnan; Thushara Thomas; Riji Thomas; Deepa K. Vijayan; Jofy. K. Paul; D. M. Vasudevan (Indian Journal of Clinical Biochemistry, 2022)

Correction to: A cost-effective and efficient approach for generating and assembling reagents for conducting real-time PCR - Ridim D Mote; Shinde Laxmikant V; Surya Bansi Singh; Mahak Tiwari; Hemant Singh; Juhi Srivastava; Vidisha Tripathi; Vasudevan Seshadri; Amitabha Majumdar; Deepa Subramanyam (Journal of Biosciences, 2022)

A cost-effective and efficient approach for generating and assembling reagents for conducting real-time PCR - Ridim D Mote; V Shinde Laxmikant; Surya Bansi Singh; Mahak Tiwari; Hemant Singh; Juhi Srivastava; Vidisha Tripathi; Vasudevan Seshadri; Amitabha Majumdar; Deepa Subramanyam (Journal of Biosciences, 2021)

Single-Turnover Variable Chlorophyll Fluorescence as a Tool for Assessing Phytoplankton Photosynthesis and Primary Productivity: Opportunities, Caveats and Recommendations - Nina Schuback; Philippe D. Tortell; Ilana Berman-Frank; Douglas A. Campbell; Aurea Ciotti; Emilie Courtecuisse; Zachary K. Erickson; Tetsuichi Fujiki; Kimberly Halsey; Anna E. Hickman; Yannick Huot; Maxime Y. Gorbunov; et al. (Frontiers in Marine Science, 2021)
Phytoplankton photosynthetic physiology can be investigated through single-turnover variable chlorophyll fluorescence (ST-ChlF) approaches, which carry unique potential to autonomously collect data at high spatial and temporal resolution. Over the past decades, significant progress has been made in the development and application of ST-ChlF methods in aquatic ecosystems, and in the interpretation of the resulting observations. At the same time, however, an increasing number of sensor types, sampling protocols, and data processing algorithms have created confusion and uncertainty among potential users, with a growing divergence of practice among different research groups. In this review, we assist the existing and upcoming user community by providing an overview of current approaches and consensus recommendations for the use of ST-ChlF measurements to examine in-situ phytoplankton productivity and photo-physiology. We argue that a consistency of practice and adherence to basic operational and quality control standards is critical to ensuring data inter-comparability. Large datasets of inter-comparable and globally coherent ST-ChlF observations hold the potential to reveal large-scale patterns and trends in phytoplankton photo-physiology, photosynthetic rates and bottom-up controls on primary productivity. As such, they hold great potential to provide invaluable physiological observations on the scales relevant for the development and validation of ecosystem models and remote sensing algorithms.

Impact of climate on the evolution of vegetation in tectonically active Karewa basin, Kashmir Himalayas - Anjum Farooqui; Suresh K Pillai; Deepa Agnihotri; Salman Khan; Rajni Tewari; Sunil K Shukla; Sajid Ali; Anjali Trivedi; S K Pandita; Kamlesh Kumar; G D Bhat; Rajesh Agnihotri (Journal of Earth System Science, 2021)

Impact of Clinically Relevant Elliptical Deformations on the Damage Patterns of Sagging and Stretched Leaflets in a Bioprosthetic Heart Valve - Deepa Sritharan; Parinaz Fathi; Jason D. Weaver; Stephen M. Retta; Changfu Wu; Nandini Duraiswamy (Cardiovascular Engineering and Technology, 2018)

Potential of native cold tolerant plant growth promoting bacilli to enhance nutrient use efficiency and yield of Amaranthus hypochondriacus - Chitra Pandey; Yogesh Kumar Negi; D. K. Maheshwari; Deepa Rawat; Deepti Prabha (Plant and Soil, 2018)

Combined effects of agrochemicals and ecosystem services on crop yield across Europe - Vesna Gagic; David Kleijn; András Báldi; Gergely Boros; Helene Bracht Jørgensen; Zoltán Elek; Michael P. D. Garratt; G. Arjen de Groot; Katarina Hedlund; Anikó Kovács‐Hostyánszki; Lorenzo Marini; Emily Martin; et al. (Ecology Letters, 2017)
Simultaneously enhancing ecosystem services provided by biodiversity below and above ground is recommended to reduce dependence on chemical pesticides and mineral fertilisers in agriculture. However, consequences for crop yield have been poorly evaluated. Above ground, increased landscape complexity is assumed to enhance biological pest control, whereas below ground, soil organic carbon is a proxy for several yield‐supporting services. In a field experiment replicated in 114 fields across Europe, we found that fertilisation had the strongest positive effect on yield, but hindered simultaneous harnessing of below‐ and above‐ground ecosystem services. We furthermore show that enhancing natural enemies and pest control through increasing landscape complexity can prove disappointing in fields with low soil services or in intensively cropped regions. Thus, understanding ecological interdependences between land use, ecosystem services and yield is necessary to promote more environmentally friendly farming by identifying situations where ecosystem services are maximised and agrochemical inputs can be reduced.

High-density lipoprotein from subjects with coronary artery disease promotes macrophage foam cell formation: role of scavenger receptor CD36 and ERK/MAPK signaling - S. Sini; D. Deepa; S. Harikrishnan; N. Jayakumari (Molecular and Cellular Biochemistry, 2017)

Climate‐induced changes in host tree–insect phenology may drive ecological state‐shift in boreal forests - Deepa S. Pureswaran; Louis De Grandpré; David Paré; Anthony Taylor; Martin Barrette; Hubert Morin; Jacques Régnière; Daniel D. Kneeshaw (Ecology, 2015)
Climate change is altering insect disturbance regimes via temperature‐mediated phenological changes and trophic interactions among host trees, herbivorous insects, and their natural enemies in boreal forests. Range expansion and increase in outbreak severity of forest insects are occurring in Europe and North America. The degree to which northern forest ecosystems are resilient to novel disturbance regimes will have direct consequences for the provisioning of goods and services from these forests and for long‐term forest management planning. Among major ecological disturbance agents in the boreal forests of North America is a tortricid moth, the eastern spruce budworm, which defoliates fir ( Abies spp.) and spruce ( Picea spp.). Northern expansion of this defoliator in eastern North America and climate‐induced narrowing of the phenological mismatch between the insect and its secondary host, black spruce ( Picea mariana ), may permit greater defoliation and mortality in extensive northern black spruce forests. Although spruce budworm outbreak centers have appeared in the boreal black spruce zone historically, defoliation and mortality were minor. Potential increases in outbreak severity and tree mortality raise concerns about the future state of this northern ecosystem. Severe spruce budworm outbreaks could decrease stand productivity compared with their occurrence in more diverse, southern balsam fir forest landscapes that have coevolved with outbreaks. Furthermore, depending on the proportion of balsam fir and deciduous species present and fire recurrence, changes in regeneration patterns and in nutrient cycling could alter ecosystem dynamics and replace black spruce by more productive mixed‐wood forest, or by less productive ericaceous shrublands. Long‐term monitoring, manipulative experiments, and process modeling of climate‐induced phenological changes on herbivorous insect pests, their host tree species, and natural enemies in northern forests are therefore crucial to predicting species range shifts and assessing ecological and economic impacts.

Safety evaluation of flubendiamide and its metabolites on cabbage and persistence in soil in different agroclimatic zones of India - K. K. Sharma; Saudamini Mohapatra; A. K. Ahuja; M. Deepa; Debi Sharma; G. K. Jagdish; N. Rashmi; R. S. Battu; S. K. Sharma; Balwinder Singh; N. S. Parihar; B. N. Sharma; et al. (Environmental Monitoring and Assessment, 2014)

A simple and efficient protocol for isolation of high quality functional RNA from different tissues of turmeric (Curcuma longa L.) - K. Deepa; T. E. Sheeja; R. Santhi; B. Sasikumar; Anu Cyriac; P. V. Deepesh; D. Prasath (Physiology and Molecular Biology of Plants, 2014)

Antifungal activity of Datura stramonium, Calotropis gigantea and Azadirachta indica against Fusarium mangiferae and floral malformation in mango - K. Usha; B. Singh; P. Praseetha; N. Deepa; D. K. Agarwal; R. Agarwal; A. Nagaraja (European Journal of Plant Pathology, 2009)

Effect of methyl isocyanate (MIC) on rat erythrocytes - Deepa Agrawal; G. S. D. Gupta; J. S. Shukla; K. K. Dutta; P. K. Ray (Archives of Toxicology, 1990)